Co-Inflammatory Roles of TGFβ1 in the Presence of TNFα Drive a Pro-inflammatory Fate in Mesenchymal Stem Cells - Lerrer, Shalom; Liubomirski, Yulia; Bott, Alexander; Abnaof, Khalid; Oren, Nino; Yousaf, Afsheen; Körner, Cindy; Meshel, Tsipi; Wiemann, Stefan; Ben-Baruch, Adit (Frontiers in Immunology, 2017)
High plasticity is a hallmark of mesenchymal stem cells (MSCs), and as such, their differentiation and activities may be shaped by factors of their microenvironment. Bones, tumors and cardiomyopathy are examples of niches and conditions that contain MSCs and are enriched with tumor necrosis factor α (TNFα) and transforming growth factor β1 (TGFβ1). These two cytokines are generally considered as having opposing roles in regulating immunity and inflammation (pro- and anti-inflammatory, respectively). Here, we performed global gene expression analysis of human bone marrow-derived MSCs and identified overlap in half of the transcriptional programs that were modified by TNFα and TGFβ1. The two cytokines elevated the mRNA expression of soluble factors, including mRNAs of pro-inflammatory mediators. Accordingly, the typical pro-inflammatory factor TNFα prominently induced the protein expression levels of the pro-inflammatory mediators CCL2, CXCL8 (IL-8) and cyclooxygenase-2 (Cox-2) in MSCs, through the NF-kB/p65 pathway. In parallel, TGFβ1 did not elevate CXCL8 protein levels and induced the protein expression of CCL2 at much lower levels than TNFα; yet, TGFβ1 readily induced Cox-2, and acted predominantly via the Smad3 pathway. Interestingly, combined stimulation of MSCs by TNFα+TGFβ1 led to a cooperative induction of all three inflammatory mediators, indicating that TGFβ1 functioned as a co-inflammatory cytokine in the presence of TNFα. The cooperative activities of TNFα+TGFβ1 that have led to CCL2 and CXCL8 induction were almost exclusively dependent on p65 activation and were not regulated by Smad3 or by the upstream regulator TAK1 (TGFβ-activated kinase 1). In contrast, the TNFα+TGFβ1-induced cooperative elevation in Cox-2 was mostly dependent on Smad3 (demonstrating cooperativity with activated NF-kB) and was partly regulated by TAK1. Studies with MSCs activated by TNFα+TGFβ1 revealed that they release factors which can affect other cells in their microenvironment and induce breast tumor cell elongation, migration and scattering out of spheroid tumor masses. Thus, our findings demonstrate a TNFα+TGFβ1-driven pro-inflammatory fate in MSCs, identify specific molecular mechanisms involved and propose that TNFα+TGFβ1-stimulated MSCs influence the tumor niche. These observations suggest key roles for the microenvironment in regulating MSC functions, which in turn may affect different health-related conditions.